Increasing Nebulizer Spray Efficiency Using a Baffle with a Conical Surface: A Computational Fluid Dynamics Analysis - Hung-Chieh Wu; Fu-Lun Chen; Yuan-Ching Chiang; Yi-June Lo; Chun-Li Lin; Wei-Jen Chang; Haw-Ming Huang (Bioengineering, 2025)
Breath-actuated nebulizers used in aerosol therapy are vital to children and patients with disabilities and stand out for their ability to accurat ely deliver medication while minimizing waste. Their performance can be measured according to the mass output and droplet size. This study aimed to analyze how the baffle impact surface geometries affect the pressure and flow streamlines inside the nebulizer using computational fluid dynamics (CFD). Computer-aided design models of conical symmetric, conical asymmetric, and arc-shaped baffle designs were analyzed using CFD simulations, with the optimal spray output validated through the differences in mass. Conical baffles exhibited superior pressure distribution and output streamlines at 0.25 cm protrusion, suggesting that the nebulizer spray performance can be enhanced by using such a conical baffle impact surface. This result serves as a valuable reference for future research.